Reply to the letter by Kondo et al: Mechanisms for new‐onset atrial fibrillation in patients with acute coronary syndrome - Mizuyoshi Nagai; Tomonori Itoh; Yoshihiro Morino (Journal of Arrhythmia, 2021)
See articles in Journal Of Arhythmia DOI: doi.org/10.1002/joa3.12233 Letter to the Editor: New‐onset atrial fibrillation after atrial ischemia